The Zionist ideas : visions for the Jewish homeland--then, now, tomorrow - Troy, Gil; Sharansky, Natan, 1948- (JPS anthologies of Jewish thought., 2018)
"The most comprehensive Zionist collection ever published, The Zionist Ideas: Visions for the Jewish Homeland --Then, Now, Tomorrow builds on Arthur Hertzberg's classic The Zionist Idea, showcasing more than 170 visionaries and shedding light on the surprisingly diverse and shared visions for realizing Israel as a democratic Jewish state"--